Natural Language Understanding and Intelligent Applications - Lin, Chin-Yew; Xue, Nianwen; Zhao, Dongyan; Huang, Xuanjing; Feng, Yansong (Springer, 2016)
This book constitutes the joint refereed proceedings of the5th CCF Conference on Natural Language Processing and Chinese Computing, NLPCC 2016, and the 24th International Conference on Computer Processing of Oriental Languages, ICCPOL 2016, held in Kunming, China, in December 2016. The 48 revised full papers presented together with 41 short papers were carefully reviewed and selected from 216 submissions. The papers cover fundamental research in language computing, multi-lingual access, webmining/text mining, machine learning for NLP, knowledge graph, NLP for social network, as well as applications in language computing